Intellectual property rights in agriculture : the World Bank's role in assisting borrower and member countries - Lele, Uma J.; Lesser, William; Horstkotte-Wesseler, Gesa. (Washington, D.C. : World Bank, 2000)
Intellectual property Rights in agriculture was the main topic of a workshop held 11-12 June, 1998 in Washington DC. The goal was to develop a better understanding of the perspectives and the challenging problems some of the key stakeholders face with regard to agriculturally related IPRs and to define possible roles of the Bank to help its borrowers / member countries.
Includes bibliographical references.
osc 01/02/2019
Loans
Keywords: Intellectual property; Agriculture; World Bank